PENGARUH PERMAINAN SUCKER BALL TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 27 PADANGTAHUN PELAJARAN 2013/2014 - Respita, Irena; K, Delsi; Sovia, Anny (Pendidikan Matematika, 2013)
This research is motivated by the studentâs understanding of mathematical concepts and learn the spirit students of SMPN 27 Padang grade VIII is still low. This study aims to determine whether studentsâ understanding of mathematical concepts with Sucker Ball game better understanding of the mathematical concepts that students apply classroom learning in the conventional SMPN 27 Padang grade VIII.This type of research is experimental, with the design of randomized trials to subjek. The population in this study were SMPN 27 Padang grade VIII that consists of seven classes listed in the school year 2013/2014. This technique take was randomly sampled, which was selected as the sample classes are VIII.3 as an experimental class and VIII.4 as control class.The instrument used in this study is a test of understanding of mathematical concepts. Form used is the essay test with a reliability test was 0,92. Data analysis techniques used were the t test of side. Based on the analysis of the data found that the two classes are normally distributed and the sample is not homogeneous. Hypothesis test results obtained t calculated= 2,47 and t table= 0,607, because t calculated > t table, so the hypothesis in this study was received. So it can be concluded that the studentsâ understanding of mathematical concepts apply sucker ball game better understanding of the mathematical concepts that students apply classroom learning in the conventional SMPN 27 Padang grade VIII academic year 2013/2014